MODEL BISNIS KANVAS UNTUK MENGEMBANGKAN TEACHING FACTORY DI SMK TATA BUSANA GUNA MENDUKUNG TUMBUHNYA INDUSTRI KREATIF - Noor Fitrihana (Jurnal Taman Vokasi, 2017)
In the strategic plan of the Ministry of Education and Culture 2015-2019, The Ministry was targeted more than 1000 SMK to develop Learning/Teaching Factory (TEFA). In other hand, according to Government rule, vocational education should have in cooperation with Professional Certification Institute (LSP), develop teaching factory (TEFA), and build competency test Center (TUK). Base on both, this paper will focus how to develop teaching factory using business model canvas in fashion design vocational high school.